Pengaruh Penerapan Sistem Informasi E-Government terhadap Transparansi dan Akuntabilitas Pengelolaan Keuangan Daerah (Studi Kasus Pada Pemerintah Kota Bandung) - Risya Nurindahsari; Rendra Trisyanto (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The number of corruption cases in the Bandung City Government that occur makes transparency and accountability very important elements in regional financial management, one way to achieve this is by providing comprehensive and complete information to the public by implementing the E-Government Information System in accordance with Instruksi Presiden No. 7 Tahun 2015 tentang Aksi Pencegahan dan Pemberantasan Korupsi. This study aims to analyze the influence of the application of the E-Government Information System on the transparency and accountability of regional financial management in 6 SKPD in the Bandung City Government so that the results can provide a reference for improvement of SKPDs that do not yet have E-Government and have not informed the public of regional financial management. This type of research uses quantitative methods with data collection techniques carried out through questionnaires. Analysis of the data used is simple linear regression analysis which is processed using SPSS version 25. The results of this study indicate that the application of E-Government Information Systems has a significant effect on Regional Financial Management Accountability by 71.2% and has an insignificant effect as much as 2.2%. on the Transparency of Regional Financial Management, while the remaining 26.6% is influenced by other factors not examined in this study.